2014
DOI: 10.1016/j.jacc.2014.01.054
|View full text |Cite
|
Sign up to set email alerts
|

Innate and Adaptive Inflammation as a Therapeutic Target in Vascular Disease

Abstract: Atherosclerosis, the main pathophysiological condition leading to cardiovascular disease (CVD), is now considered to be a chronic inflammatory condition. Statins are the most widely used and promising agents in treating CVD and are renowned for their pleiotropic lipid-lowering independent effects. Statins exert their anti-inflammatory effects on the vascular wall through a variety of molecular pathways of the innate and adaptive immune systems, their impact on the circulating levels of pro-inflammatory cytokin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
120
1
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(125 citation statements)
references
References 86 publications
1
120
1
3
Order By: Relevance
“…AS commonly initiates within the arterial wall primarily as a result of the destruction occurring in endogenously structures, which can be attributed to several matters, such as hypertension, smoking, oxidized low-density lipoprotein (ox-LDL) and so forth [3-5]. Ox-LDL, as the most important factor contributing to the development of AS, can activate both the innate and adaptive immune responses with the differentiation from monocytes to macrophages and the unregulated phagocytic activity of macrophages [6-8], subsequently induce the accumulation of lipid and the formation of foam cells, which is the hallmark event of AS [9, 10]. …”
Section: Introductionmentioning
confidence: 99%
“…AS commonly initiates within the arterial wall primarily as a result of the destruction occurring in endogenously structures, which can be attributed to several matters, such as hypertension, smoking, oxidized low-density lipoprotein (ox-LDL) and so forth [3-5]. Ox-LDL, as the most important factor contributing to the development of AS, can activate both the innate and adaptive immune responses with the differentiation from monocytes to macrophages and the unregulated phagocytic activity of macrophages [6-8], subsequently induce the accumulation of lipid and the formation of foam cells, which is the hallmark event of AS [9, 10]. …”
Section: Introductionmentioning
confidence: 99%
“…The main vascular features of the inflammatory response are vasodilation, increased vascular permeability, endothelial expression of adhesion molecules, and chemokine production [38]. Accordingly, an increased number of dilated capillaries and increased expression of ICAM-1 Fig.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that statins promote the differentiation of Tregs (212), and restrain the differentiation of Th 17 (213). Kruppel-like factor 2 (KLF2), which regulates the expression of molecules essential for naive T cell recirculation and the maintenance of T cell quiescence, plays a key role in this mechanism (214).…”
Section: Inflammationmentioning
confidence: 99%